Pregnancies and their results in phase III and IV clinical trial participants in Peru - Palomino Flores, Christian (2020)
Objectives: To identify the occurrence of cases of pregnancy, births and abortion in participants of clinical trials in phases III and IV, in Peru. Methods: Retrospective secondary data analysis study of all cases of pregnancy that occurred during clinical trials, in the period 2010 to 2015. The data were obtained from the virtual system REAS-NET, of the National Institute of Health for the report of serious adverse events. The Fisher and Chi square test was used to analyze the variables. Results: 30 cases of pregnancies of patients enrolled in clinical trials were found, 24 of them in phase III trials. The age range was 19 to 44 years, 21 cases ended in abortion. None of the variables studied presented a significant association with the outcome of pregnancy: abortion and normal live birth. Conclusions: Pregnancies were found in the participants in phase III and IV clinical trials, the age corresponded to the fertile age of the women.